Efektivitas Penggunaan Teknologi Sosial Media Whatsapp terhadap Minat dan Hasil Belajar Dimasa Pandemi Covid-19 Sekolah Dasar - Nurmawaddah, Nurmawaddah; Thahir, Irmawati; Jais, Mudeing; Ampry, Evy Segarawati (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
The purpose of this study was to determine the effectiveness of the use of WhatsApp social media technology on students' interests and learning outcomes during the Covid-19 pandemic at SD Inpres 3/77 Massila, Bone Regency. The type of research used is ex post facto research. This research was conducted from 24 May 2022 to 24 July 2022. The population in this study were all students of SD Inpres 3/77 Massila, Bone Regency, totaling 81 people. The subjects of this study were students of grades IV, V and VI at SD Inpres 3/77 Massila, Bone Regency, with a total of 35 students. Data collection techniques in the form of interviews, questionnaires (questionnaire) and documentation. With data analysis techniques using descriptive statistical analysis, path analysis and inferential statistical analysis. To analyze the data using the SPSS version 25 program. The results showed that the use of whatsapp social media was effectively used for students' interests and learning outcomes during the Covid-19 pandemic SD Inpres 3/77 Massila, Bone Regency. From the data obtained, based on the results of descriptive analysis, the results show the average value (mean) of the variable X regarding the use of whatsapp is 28 which lies in the interval 28.5-29.5 with high qualifications. For the average value (mean) of the Y1 variable regarding student interest in learning, namely 67 which lies in the interval 67.5-68.5 with high qualifications. While the average value (mean) of the Y2 variable regarding student learning outcomes is 91 which lies in the 94-100 interval with high qualifications. Furthermore, linear regression analysis shows that the variable using whatsapp (X) is significantly effective on learning interest (Y1) with a value of 0.000. WhatsApp use variable (X), interest in learning (Y1) is not significantly effective on learning outcomes (Y2) with a value of 0.122. The whatsapp usage variable (X) is significantly effective on learning outcomes (Y2) with a value of 0.042.